PENGARUH LINGKUNGAN KELUARGA TERHADAP PENILAIAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (STUDI KORELASIONAL PADA SISWA KELAS X PERHOTELAN) - Kaka Habibi; Tarpan Suparman; Ajat Sudrajat (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
The purpose of this study is to determine whether there is an influence of the family environment on the assessment of Islamic Religious Education learning outcomes in Class X Hospitality Students of State Vocational High School 2 Karawang. This type of research uses quantitative descriptive research. The object of this study is Class X Hospitality Students of State Vocational High School 2 Karawang. The population in this study was 70 students. Regarding data collection techniques using questionnaires and documentation. Based on the data analysis that has been done, it is known that the family environment influences learning outcomes in Islamic Religious Education learning in Class X Hospitality Students of State Vocational High School 2 Karawang. It is known that the results of the hypothesis test with a significance value of 0.001 <0.05 means that variable X influences variable Y. The calculated t value of 8.725> t table 1.995, meaning that the family environment variable (X) influences the learning outcome variable (Y). The level of relationship between the family environment and the assessment of student learning outcomes in the learning process of Islamic Religious Education in Class X Hospitality Students of State Vocational High School 2 Karawang is in the low category.